2015
DOI: 10.2147/jaa.s76639
|View full text |Cite
|
Sign up to set email alerts
|

Long-acting muscarinic antagonist use in adults with asthma: real-life prescribing and outcomes of add-on therapy with tiotropium bromide

Abstract: BackgroundRandomized controlled trials indicate that addition of a long-acting muscarinic antagonist (LAMA) such as tiotropium may improve asthma control and reduce exacerbation risk in patients with poorly controlled asthma, but broader clinical studies are needed to investigate the effectiveness of LAMA in real-life asthma care.MethodsMedical records of adults with asthma (aged ≥18 years) prescribed tiotropium were obtained from the UK Optimum Patient Care Research Database for the period 2001–2013. Patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 17 publications
3
11
0
Order By: Relevance
“…However, improvements in Asthma Control Questionnaire (ACQ)-7 and Asthma Quality of Life Questionnaire (AQLQ) scores were small and inconsistent, and did not reach a clinically important difference. Similar results were reported in a real-life asthma population, where the addition of tiotropium was associated with significant decreases in the incidence of exacerbations (from 37% to 27%) and antibiotic prescriptions for lower respiratory tract infections [ 36 ]. Tiotropium (soft-mist inhaler) has recently been included as a new add-on treatment for GINA Steps 4 and 5 in patients aged ≥18 years with a history of exacerbations (Evidence A) [ 18 ].…”
Section: Treating Severe Asthma: Current Optionssupporting
confidence: 83%
“…However, improvements in Asthma Control Questionnaire (ACQ)-7 and Asthma Quality of Life Questionnaire (AQLQ) scores were small and inconsistent, and did not reach a clinically important difference. Similar results were reported in a real-life asthma population, where the addition of tiotropium was associated with significant decreases in the incidence of exacerbations (from 37% to 27%) and antibiotic prescriptions for lower respiratory tract infections [ 36 ]. Tiotropium (soft-mist inhaler) has recently been included as a new add-on treatment for GINA Steps 4 and 5 in patients aged ≥18 years with a history of exacerbations (Evidence A) [ 18 ].…”
Section: Treating Severe Asthma: Current Optionssupporting
confidence: 83%
“…Medical records of adults with asthma who were prescribed tiotropium were obtained from the UK Optimum Patient Care Research Database for the period 2001–2013 [ 25 ]. Two primary outcomes were compared in the year before (baseline) and the year after (outcome) addition of tiotropium: exacerbations (i.e.…”
Section: Resultsmentioning
confidence: 99%
“…A retrospective study of 2042 adults with asthma found that, in the first year following the addition of tiotropium (93% via HandiHaler, 7% via Respimat at 5 μg), there was a decrease in the incidence of both primary outcomes of exacerbations (patients experiencing ≥1 exacerbation were decreased from 37 to 27%, p < 0.001) and respiratory events requiring antibiotic prescriptions (from 58 to 47%, p < 0.001) [ 59 ]. Unlike the earlier-presented data from the Phase III randomized trials, no significant changes in lung function were found with the addition of tiotropium; this negative finding may be related to the inclusion of smokers (∼50% had an active smoking history, whereas those with >10 pack-year smoking history were excluded from trials) and the limited control on lung function data inherent to a retrospective study including timing of the measurements with regard to time of day, or relative to tiotropium initiation [ 59 ]. In a randomized, open-label, parallel-group pragmatic trial of 1070 black adults with moderate-to-severe asthma, the effect of tiotropium HandiHaler as add-on therapy to ICSs on time to first exacerbation was compared with LABAs (salmeterol or formoterol) [ 46 ].…”
Section: Further Perspectivesmentioning
confidence: 99%